Caso de estudio: propuesta de un plan estratégico en la empresa J.K. You World Importación y Exportación E.I.R.L del sector juguetero - Estrada Escajadillo, Gian Franco (2023)
The objective of this professional sufficiency work is to optimize the business model of J.K. You World, a company dedicated to the retail and wholesale sale of children's toys and baby products, through the development of a strategic proposal for the company. The development of the study is divided into four chapters in order to propose strategies that will guide the company to achieve its objectives. The first chapter comprises the internal and external strategic diagnosis of the company, in which, first of all, the analysis of the business model, the investigation of the value chain, the definition of the company's competitive advantages, and the analysis of its strengths and weaknesses were carried out. Subsequently, the PEST analysis, Porter's five forces, and the determination of the opportunities and threats of the environment in which the company is involved were carried out. The second chapter deals with strategy formulation, in which the EFI and EFE arrays are involved, the formulation of the generic business strategy matrix and the development of the PEYEA, FODA and MPC arrays were carried out. The company's vision, mission, policies and strategic objectives were also defined. The third chapter covers the strategic implementation where the redesign of the company's organizational structure and the approach of changes for the introduction of strategies at the functional, business, corporate and intensive levels were developed. The fourth chapter includes the strategic control where the design of a Strategic Control Map is established and the development of a Balanced Scorecard in which the strategic objectives of "Juguete Kids" are detailed.